Formation of general instrumental competence of engineering teaching professionals based on the informational and educational computer-based means: state of the problem - Yaschun, T; Gromov, E (Problems of Engineer-Pedagogical Education, 2019)
The current state of the education system in Ukraine is at the stage of complete reorganization which is bringing about changes in the ideology of training. Regulatory documents serve as a source for the reorganization of educational content. The main one is the industry standard of higher education. From mere provision of knowledge and skills, modern education is moving towards the formation of competences, including instrumental ones, aimed at the practical activities of future specialists. General instrumental competence of future computer specialists should be acquired within the basic computer training. The paper considers both the general concept of competence and the main components of instrumental competence. Activity and personality-oriented approaches aimed at its effective formation are subject to analysis. The authors conduct a search for new approaches to the organization, management and informational support necessary to teach fundamentals of professional use of computer technologies and carry out a selection of the ones which meet the requirements of training in the field of “Vocational education” in the first years of studying. The article considers the possibilities of using information and computer technology in laboratory work and highlights the tendency to abandon traditional lectures on computer disciplines and enrich lecturing methodology with multimedia and large-scale demonstration of educational presentations, real-time communication, use of video conferences, distance learning, technical implementation options, informational and methodological content of cloud-oriented informational and educational environments during basic computer training. The results of the analytical review allow mapping out the ways of practical implementation of the authors‟ complex of informational and educational computer-based means aimed at the formation of a system of competences that provide future specialists with the skills necessary to use information and computer technology in professional activities.